Integrating Multiple Intelligences and Qur’anic Values in Arabic Language Learning: A Student-Centered and Spiritual Approach - Maulidiya, Amanda; Ali, Mad (Himpunan Mahasiswa Program Studi (HMPS) Pendidikan Bahasa Arab Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Negeri (IAIN) Jember, 2025)
Traditional Arabic language instruction in Islamic educational institutions often employs conventional approaches focused on memorization and grammar mastery, neglecting students' diverse learning potentials and spiritual development. Despite separate studies on Multiple Intelligences in language teaching and Qur'anic values in education, research comprehensively integrating these approaches in Arabic pedagogy remains scarce. This study aimed to design an Arabic language learning model that synthesizes Gardner's Multiple Intelligences theory with Qur'anic values for holistic student development. Using a descriptive qualitative methodology through library research, data were collected from scientific journals, books, and Qur'anic texts. Analysis employed an inductive-based thematic approach (al-tahlil al-istiqra'i) involving identification of key themes, categorization, cross-source synthesis, and conceptual conclusion drawing. Findings revealed that this integrated approach creates a student-centered, spiritually enriched learning environment that accommodates diverse cognitive profiles while internalizing Islamic principles. Implementation strategies for the four language skills (istima', kalam, qira'ah, kitabah) demonstrated enhanced student engagement and improved language acquisition when tailored to students' dominant intelligences and embedded with Qur'anic values. This model contributes a novel pedagogical framework that addresses limitations of traditional approaches while promoting both linguistic proficiency and Islamic character formation.